From Puritanism to Platonism in Seventeenth Century England - Roberts, James Deotis. author. aut Link
298 p.
Keywords: The research of Professor J. D. Roberts has interested me for several years. It has interested me because he has been working in a really rich area of intellectual history. Even before Professor Whitehead taught us to speak of the seventeenth century as the "century of genius," many of us looked with wonder on the creativity of the men who produced religious and philosophical literature in that period of contro versy and of power. It was, in a most unusual way, a flowering time of the human spirit. The present volume is devoted to one fascinating chapter in the history of ideas. We know now, far better than we knew a generation ago, how incendiary Puritan ideas really were. They had tremendous consequences, many of which continue to this day, in spite of the absurd caricature of Puritanism, which is popularly accepted. The best of Milton's contemporaries were great thinkers as well as great doers.